1999
DOI: 10.1021/np990285x
|View full text |Cite
|
Sign up to set email alerts
|

New Carbazole Alkaloids from Clausena anisata with Antitumor Promoting Activity

Abstract: Four new carbazole alkaloids, named clausamine D (1), E (2), F (3), and G (4), were isolated from Clausena anisata as inhibitors of Epstein-Barr virus early antigen activation induced by 12-O-tetradecanoylphorbol-13-acetate in Raji cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 9 publications
3
48
0
Order By: Relevance
“…SAR analysis of antitumor carbazole alkaloids showed that the prenyl group at C-4 plays an important role in the inhibitory activity. 72) Moreover, a new nitro-containing tetrahydroprotoberberine, (−)-2,9-dihydroxyl-3,11-dimethoxy-1,10-dinitrotetrahydroprotoberberine (45), and five isoquinoline alkaloids, (+)-1-nitroapocavidine (46), berberine (47), palmatine (48), dehydrocavidine (49), and sanguinarine (50) (Fig. 8), were isolated from the whole plant of C. saxicola.…”
Section: Sar Studies On the Pharmacological Activity Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR analysis of antitumor carbazole alkaloids showed that the prenyl group at C-4 plays an important role in the inhibitory activity. 72) Moreover, a new nitro-containing tetrahydroprotoberberine, (−)-2,9-dihydroxyl-3,11-dimethoxy-1,10-dinitrotetrahydroprotoberberine (45), and five isoquinoline alkaloids, (+)-1-nitroapocavidine (46), berberine (47), palmatine (48), dehydrocavidine (49), and sanguinarine (50) (Fig. 8), were isolated from the whole plant of C. saxicola.…”
Section: Sar Studies On the Pharmacological Activity Ofmentioning
confidence: 99%
“…Further SAR studies demonstrated that the increase in anti-AchE activity was attributed to the nitro-substituent at ring A in the tetrahydroprotoberberines. 72) In addition, three berberine alkaloids from Coptis chinensis, berberine (47), coptisine (51), and palmatine (48) (Fig. 7), were evaluated for their inhibitory activity against Escherichia coli.…”
Section: Sar Studies On the Pharmacological Activity Ofmentioning
confidence: 99%
“…348 Clausamine G 583 containing a hydroperoxy moiety in the molecule, is the first example of the isolation of a peroxygen-ated carbazole alkaloid in nature. 349 The leaves of Piper aduncum afforded an prenylated benzoic acid derivative 584 with antifungal activity whilst the related 585 was obtained from the aerial parts of Aster spathulifolius. The presence of a hydroperoxide group at the side chain could be directly associated to its fungitoxicity.…”
mentioning
confidence: 99%
“…The growing knowledge on the relation between apoptosis and carcinogenesis has made it possible to develop novel approaches to treat cancer. Carbazole alkaloids are well-known in nature (11) and some of these compounds possess anticancer activity (12)(13)(14)(15)(16). ·-Carboline can be regarded as a bioisostere of carbazole with the benzene ring of carbazole replaced by a pyridine ring.…”
Section: Introductionmentioning
confidence: 99%